ROMAN RELIGIOUS BUILDINGS IN NORTH AFRICA - Ahmed Demmana; Ali Ben Thabet (International Journal of Innovative Technologies in Social Science, 2025)
Roman architecture has long been a subject of interest for researchers in the fields of history and archaeology, as the Romans were able to leave a lasting cultural imprint wherever they established settlements. One of the most remarkable features of this architecture lies in the diversity of its elements and the precision of its details, particularly in the artistic expression of places of worship within the Roman city.During the Roman occupation, North Africa became a prominent stage for such architecture, with some of its ancient cities serving as true repositories of Roman architectural traditions. Cities such as Timgad, Thubursicum, and Lambaesis clearly reflect the characteristics of these structures. The types of buildings varied according to their function, including temples, altars, shrines, tombs, and funerary monuments. The Romans devoted significant effort to the construction of these buildings, carefully highlighting the role of their gods in daily life.